2017
DOI: 10.3732/ajb.1700057
|View full text |Cite
|
Sign up to set email alerts
|

Carbon allocation to growth and storage in two evergreen species of contrasting successional status

Abstract: In low light, prioritized C storage instead of growth, whereas prioritized growth and lateral branching. Our results suggest that shade tolerance depends on efficient light capture rather than C conservation traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…While this study suggests that the rebuilt of storage after drought does not occur at the expens of growth, droughts could cause C storage reductions in other systems, particularly in isohydric species (McDowell et al, 2008(McDowell et al, , 2011Brodribb et al, 2014). In such cases, C replenishment could take place earlier than growth recovery, similarly to what has been observed following periods of severe defoliation (Palacio et al, 2012;Piper et al, 2015Piper et al, , 2017bWiley et al, 2017). Post-drought responses of C allocation could also depend on tree age.…”
Section: Introductionmentioning
confidence: 58%
“…While this study suggests that the rebuilt of storage after drought does not occur at the expens of growth, droughts could cause C storage reductions in other systems, particularly in isohydric species (McDowell et al, 2008(McDowell et al, , 2011Brodribb et al, 2014). In such cases, C replenishment could take place earlier than growth recovery, similarly to what has been observed following periods of severe defoliation (Palacio et al, 2012;Piper et al, 2015Piper et al, , 2017bWiley et al, 2017). Post-drought responses of C allocation could also depend on tree age.…”
Section: Introductionmentioning
confidence: 58%
“…Nonetheless, although growth is rarely C limited under natural conditions, tree survival could be. For example, disturbances that involve the removal of photosynthetic tissues, like folivory or fire, reduce C storage by reducing the C returns of the removed leaf cohort and by supporting regrowth before stores had achieved full C replenishment [16][17][18]. Additionally, regrowth after severe folivory is often sparse and characterized by smaller and nutritionally poorer leaves than the foliage lost to herbivores [19,20], in turn rendering low C return.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have found evidence linking seedling shade tolerance to carbon allocation to storage (Canham et al 1999, Kitajima 1994, Poorter and Kitajima 2007, several others did not (Canham et al 1999, Lusk and Piper 2007, Piper 2015, Piper et al 2009, 2017. One possible explanation for the discrepancy is that, in some regions, the levels of understorey herbivory are insufficient to select for herbivory tolerance.…”
Section: Introductionmentioning
confidence: 71%